Improving The Vocabulary Mastery of The Eight Year Students of SMP Negeri 13 Parepare Through Fan-N-Pick Technique - Ambia, Chairul (Pusat Pengembangan Publikasi dan Hak Kekayaan Intelektual Universitas Muhammadiyah Parepare, 2018)
Vocabulary is one of the language components that should be mastered by student from the elementary school up to university. If the students do not recognize the meaning of the words they will be unable to participate in conversation. Therefore, the students firstly should master a large number of vocabularies, without having this, the students cannot express their ideas clearly and effectively. Those become some of the considerations of the researcher to conduct this research when doing an observation at SMP Negeri 13 Parepare since the students show very poor achievement in vocabulary mastery. In this case, the researcher initiatives to solve the lack of students’ vocabulary mastery by implement one of innovative learning technique that is fan-n-pick tecknique. Then, the objective of the research is to find out whether or not fan-n-pick can improve vocabulary mastery of the eight year students of SMP Negeri 13 Parepare. significantly. The researcher applied quasi-experimental method, with two group pre-test and post-test design. The test form was vocabulary test that related to the procedure text which multiple choice test consists of 10 numbers, translate word into Indonesia consists of 10 numbers and fill the blank test consists of 5 numbers. The samples were chosen by using random sampling technique which consisted of 15 students from two classes taken from the population of the eight year students of SMP Negeri 13 Parepare. The total number of population was 15 students. The result of the data analysis shows that the students’ vocabulary mastery improved significantly. It showed by the mean score in experimental class of pre-test was 14.4 and the post-test was 33.7. It shows that the implementation of fan-n-pick technique can improve the vocabulary mastery of the eight year students of SMP Negeri 13 Parepare significantly. Besides the different score of pre-test and post-test, the mean score of the students in post-test was 0.00 is higher than the PERMENDIKBUD (75) in SMP Negeri 13 Parepare. After analyzing the data by using the t-test formula, the result of t-test value in post-test was 0.05 and t-table value was 0.00. It means that t-test value (0.00) was higher than t-table value (0.05). Those indicate that H1 was accepted and H0 was rejected and the students who were taught through fan-n-pick technique are better than the students who were taught through showdown technique.